Graduate Work-Readiness in Mauritius: A multi-stakeholder approach - Hardin-Ramanan, Sarita; Gopee, Shafiiq; Rowtho, Vikash; Charoux, Odylle (2020)
Characterised by strong human capital dependency, Small Island Development States (SIDS) such as Mauritius depend largely on work-ready graduates to boost their economy. Yet, Graduate Work Readiness (GWR) and graduate unemployment feature prominently on the Mauritian government agenda. This paper investigates the previously unexplored issue of GWR in Mauritius through four key stakeholder lenses - those of the government, employers, universities, and undergraduates - before suggesting collaborative strategies to enhance graduate employability. The paper findings build on government and parastatal body interviews and qualitative survey responses from the Top 100 companies, higher education institution directors and final year undergraduates in Mauritius. Study results and recommendations are derived from a thematic content analysis of interview transcripts and qualitative survey data. Results indicate that there is a strong need to (1) strengthen stakeholder links, (2) enforce industry-centric university curricula, (4) improve graduate work experience, (4) hone graduate soft skills, and (5) their attitude to work. A Graduate Work Readiness Integrated Stakeholder Framework (GWRISF) supported by a National Work Integrated Learning Committee (NWILC) is then recommended. It is envisaged that proposed strategies will not only assist Mauritian stakeholders in better joining forces for GWR improvement but can also be useful to other comparable SIDS.